Optimize the maximum flow of electricity capacity using Ford Fulkerson, Edmonds Karp and Goldberg Tarjan algorithm / Nik Nur Diyana Nik Mohd Huzaidi - Nik Mohd Huzaidi, Nik Nur Diyana (2024)
This research explores the optimization of electricity flow using the Ford Fulkerson, Edmonds Karp, and Goldberg Tarjan algorithms. The main goals are to study these algorithms for maximum electricity flow, implement them to find the best flow in electricity transmission, and optimize the flow using these methods. The process involves transforming data into a residual graph representing electricity flow through substations and power lines, then applying the algorithms step by step to determine maximum flow capacity. The result and conclusion show that Ford Fulkerson and Edmonds Karp achieve a maximum flow of 2500 MW, while Goldberg Tarjan achieves 2400 MW. The time complexity and execution time of each algorithm are analyzed and discussed. However, Goldberg Tarjan is more efficient in terms of time complexity and execution time. Despite a slightly lower flow, it processes faster and handles larger, more complex networks better, making it the best choice for optimizing power transmission.